Clinical experience with wearable cardioverter defibrillators at a tertiary electrophysiology program. Issue 11 (29th September 2018) - Bossory, Laurie; Schubert, Scott; Afzal, Muhammad R.; Weiss, Raul; Tyler, Jaret; Kalbfleisch, Steven; Augostini, Ralph; Hummel, John; Okabe, Toshimasa; Daoud, Emile G.; Houmsse, Mahmoud
Abstract: Background: A wearable cardioverter defibrillator (WCD) is an alternative for patients who are not immediate candidates for an implantable cardioverter defibrillator (ICD). Methods: Retrospective analysis of 242 patients prescribed a WCD from January 2014 through March 2015 with 1‐year follow‐up. Results: A WCD was prescribed to 242 patients during the 15‐month period. Forty‐one patients were excluded due to lack of complete follow‐up. The remaining 201 patients received a WCD for primary or secondary prevention of SCD. Seventy‐nine percent of WCDs were prescribed by nonelectrophysiologists. Underlying etiologies for the WCD prescription included: 38% nonischemic cardiomyopathy, 25% recent myocardial infarction, 16% newly diagnosed ischemic cardiomyopathy, 12% documented ventricular arrhythmia, 6% ICD lead extraction, and 3% had high risk conditions for sudden cardiac death. During 1‐year follow‐up, 96 patients (48%) received an ICD and five patients (2.5%) received appropriate shocks and one patient (0.5 %) received an inappropriate shock. Other 105 (52%) patients subsequently did not require an ICD due to either improvement in ejection fraction, refusal of ICD therapy, or death. Conclusions: About half of patients prescribed a WCD subsequently receive an ICD and the rate of appropriate shock therapy from the WCD is 2.5%.